2012
DOI: 10.1007/s00234-011-1001-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic gray matter changes of adolescents with anorexia nervosa in combined MR proton and phosphorus spectroscopy

Abstract: Significant changes in GM metabolite concentrations were observed in AN possibly triggered by elevated excitotoxin Glu. Increased tCho may indicate modifications of membrane phospholipids due to increased catabolism in the parietal region. Since no significant changes in phosphorylated choline compounds were found for the frontal region, the tCho increase in this region may hint to fluidity changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 90 publications
4
33
0
Order By: Relevance
“…Nonetheless, it is tempting to speculate that AN could result in changes in the size of neurons, glia or in metabolic processes (19). Indeed, neurohistological evidence exists suggestive of AN-related alterations in dendritic spine morphology and density (78,79) and a recent MR spectroscopy study found increased concentrations of potentially excitotoxic metabolites (glutamate) selectively in gray matter (80).…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, it is tempting to speculate that AN could result in changes in the size of neurons, glia or in metabolic processes (19). Indeed, neurohistological evidence exists suggestive of AN-related alterations in dendritic spine morphology and density (78,79) and a recent MR spectroscopy study found increased concentrations of potentially excitotoxic metabolites (glutamate) selectively in gray matter (80).…”
Section: Discussionmentioning
confidence: 98%
“…Malnutrition in AN is associated with changes in brain structure (e.g., reduction in gray matter, altered white matter integrity) and profound metabolic, electrolyte, and endocrine disturbances. [106][107][108][109][110] Studies in animals suggest that diet and weight can influence DA 111, 112 and 5-HT metabolism. 61 Strategies to avoid the confounding effects of abnormal nutritional status include: 1) characterizing behavioral traits that occur in childhood, prior to the onset of an ED, and 2) studying recovered anorexics, although it remains conjectural whether abnormal findings reflect traits or scars.…”
Section: State and Trait In Anmentioning
confidence: 99%
“…10 The relative amount of gray matter, white matter, and cerebrospinal fluid contributing to the individual voxel was calculated using MATLAB scripts. 31 P and 1 H magnetic resonance spectra from a patient with left middle cerebral artery (MCA) stroke.…”
Section: Data Processingmentioning
confidence: 99%